Gambaran Fungsi Jantung Kelinci Domestik Secara Ekhokardiogram pada Anestesi Propofol dan Isoflurane Jangka Panjang (ECHOCARDIOGRAM PROFILE OF CARDIAC FUNCTION IN DOMESTIC RABBITS DURING LONG-TERM ANESTHESIA PROPOFOL AND ISOFLURANE) - Siallagan, Sitaria; ., Gunanti; Noviana, Deni (Jurnal Veteriner; Vol 15 No 2 (2014), 2014)
Several major surgeries may require long time use of anesthetics and therefore increase the heartfunction suppression. The purpose of this study was to determine long term effects of anesthetic propofoland isoflurane on heart structure and function of domestic rabbits through observation of the blood flowvolume and contraction capabilities by M-mode echocardiography examination. This study used thecombination of propofol 12.5 mg/kg IV as an induction and isoflurane inhalation as the maintenanceanesthetic for a 12-hour observation. Parameters observed in this study were heart rate, wall thickness,internal chamber dimension, blood flow volume, fractional shortening, and ejection fraction. Results showedthat the left ventricle heart chamber dimensions during diastole (LVIDd) and systole (LVIDs) were between1.21±0.08 to 1.33±0.1 cm, and 0.87±0.08 to 0.98±0.08 cm respectively. Left ventricular wall thickness atdiastole (LVWd) and systole (LVWs) ranged from 0.24±0.04 to 0.28±0.04 cm, and 0.23±0.03 to 0.28±0.05cm respectively, while the thickness of the interventricular septa at diastole (IVSd) and systole (IVSs)ranged from 0.23±0.02 to 0.27±0.04 cm, and 0.28±0.06 to 0.30±0.05 cm. Heart rate ranged from 244.6±18.46to 266.4±24.55 beat/min. Heart flow volumes which included stroke volume (SV) and cardiac output (CO)ranged from 1.07±0.29 to 1.57±0.53 mL/beat and 0.27±0.07 to 0.39±0.14 L/min respectively. Fractionalshortening and ejection fraction ranged from 26±3 to 31±5% and 60±2 to 67±8% respectively. In conclusion,long term anesthesic of propofol and isoflurane combination induced minimum cardiac suppression indomestic rabbits.
Keywords: long time anesthesia, echocardiography, heart function, rabbits